Developing a life skills-based teaching factory model for kejar paket C photography training - Alvian Pramadani Hestyan; Yatim Riyanto; Rofik Jalal Rosyanafi (Journal of Educational and Learning Studies, 2026)
This study aimed to develop and validate a life skills-based teaching factory model for photography training in the Kejar Paket C equivalency program to address the limited application of teaching factory in nonformal education. The study employed development research using the Four-D (Define, Design, Develop, Disseminate) model. The model was tested through limited and wider field trials involving learners from two Community Learning Centers in East Java. Data were collected using validated instruments and analyzed through expert validation, paired-sample t-tests, and normalized gain scores. The model was rated highly feasible and practical by experts, tutors, and learners. It also produced significant improvements in cognitive, psychomotor, and affective learning outcomes across both trial stages. The life skills-based teaching factory model is feasible, practical, and effective for photography training in nonformal equivalency education, providing an evidence-based framework for integrating vocational competence and life skills within Community Learning Centers.